PSIII-22 Fermentation characteristics of xylo- and manno-oligosaccharides and soluble and insoluble arabinoxylan studied using an in vitro model of swine. (7th December 2018) - Tiwari, U; Jha, R
Abstract: Fermentation substrate modulates the composition of microbial community and the end products of microbial metabolism. Xylo-oligosaccharide (XOS) and manno-oligosaccharide (MOS) are newly developed functional oligosaccharides or the prebiotics produced from xylan and mannan, respectively by enzymatic hydrolysis that has a lot of beneficial immunological and health effects. Depending upon the number of xylose or mannose residues in their back bone they are named as xylobiose (2 xylose residue), mannotriose (3 mannan residue) and so on. These XOS and MOS are linked together by β-glycosidic bond of the linear polyxylose or polymannose chains. Two independent studies were carried out using an in vitro model. In study 1, 5 XOS and 5 MOS of chain length of 2 to 6 to evaluate if the chain length affects fermentation characteristics. In study 2, pure soluble and insoluble arabinoxylan (AX) with or without supplemental xylanase were used to evaluate the role of xylanase in degrading soluble and insoluble AX. Samples were fermented using fresh pig feces as microbial inoculum and gas production were recorded periodically for 72 h by means of a pressure transducer and modeled mathematically. The XOS increased ( P < 0.05) total gas production. The MOS produced higher ( P < 0.05) amount of butyrate compared to XOS. Among XOS, xylotriose produced higher ( P < 0.05) amount of butyrate. Among MOS, manno-hexaose produced higher ( P < 0.05) amount of butyrate. Soluble AX produced higher ( P < 0.05) amount of butyrate than insoluble AX. Supplemental xylanase in soluble AX produced higher ( P < 0.05) VFA. Hence, MOS is more potent butyrogenic substrate than XOS. Smaller chain length of XOS produced more butyrate whereas larger chain length of MOS produced more butyrate. In conclusion, chain length XOS and MOS affect production of VFA as an in vitro swine model as well as butyrate.